Patient profile and treatment pattern characterization of advanced melanoma at two private cancer centers in brazil: a real-world study - Finardi Roubik, Camila; Casagrande Drozda Oliveira, Ana Paula; Araujo Mirandola Tieppo Ferreira, Daniela; Herrero Geraldino, Thais; Neves de Carvalho, Leticia Maria; Cunha De Sousa Martins, Cicero Luiz; Ladislau, Leandro (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To analyze the profile of advanced melanoma patients and treatment patterns at two private oncology centers in Brazil. Methods: This retrospective observational study analyzed the profile of advanced melanoma patients and treatment patterns at two pri vate oncology centers in Brazil: COI Américas – RJ and Hospital Paulistano - SP. Patients with a diagnosis of advanced melanoma (stage III or IV) who received at least one sys temic treatment between 2012 and 2020 were included. Demographic and clinical in formation was collected from medical records and analyzed using SPSS v25.0 software. Results: The study included 185 patients, with a mean age of 62.8 years and an average weight of 78 kg. Throughout the study period, the predominant first-line treatment was anti-PD-1 monotherapy, followed by dacarbazine. For patients treated up until 2015, dacarbazine was the primary first-line choice; however, starting in 2016, immunotherapy became the most common initial therapeutic approach. The combination of anti-PD-1 with anti-CTLA-4 was also a relevant option. Conclusion: The study highlights the shift in treatment patterns for advanced melanoma in Brazil with the introduction of immuno therapy and suggests that the evolution of treatment should continue to be monitored in the future with more comprehensive studies.